Supplementation of Indigenous Probiotic Bacteria into Yoghurt - Lily Arsanti Lestari; Eni Harmayani; Y. Marsono (Indonesian Association of Food Technologists, 2003)
Traditional youhurt bacteria, lactobacillus bulgaricus and streptococcus thermohhilus, usually do not survive under acidic conditions and bile concentrations when they encountered in the gastrointestinal tract.Therefore for yughurt to be considered as aprobiotic productct, probiotic bacteria are incorporated as a dietary adjunct.The purpose of this research was to produce acceptable yougurt supplemented with indigenous probiotic bacteria.This research was divied into three parts i.e.addition of indigenous probiotic(Lactobacillus sp.Dad 13 and lactobacillus plantarum Mut7) in standart formula, sensory evalution of yoghurt on appearance, texture, flavor, and everall, and evalution of selected probiotic culture for its viability and capability to grow with yoghurt starter.Lactobascillus sp Dad 13 and lactocillus plantarum Mut 7)in standart formula, sensoriy evalution of youghurt on appearence, texture, flavor, and overall and evalution of selected probiotic culture for its viability and capability to grow with yoghurt starter.Lactobcillus sp dad 13 and lactobacillus plantarum Mut7 were selected as indigenous probiotic culture for its viability and capability to grow with yoghurt starter.Lacrobacillus sp Dad 13 and Lactobacillus plantarum Mut7 were selected as indigeneous probiotics such as acid and bile tolerant, capable of supressing enteric pathogenic bacteria, improving lactic acid bacteria population in colon and also have the ability to lower cholesterol levels.The result s showed that lactobacillus sp.dad 13 produced better flavor compared with yohurt supplemnted with L.plantarum Mut7 and traditional yoghurt without probiotic suplementation. However, suplementation of lactobacillus sp Dad 13 produced lower sensory score on appearance, but similar in texture compared with traditional yoghurt.Supplementation of lactobacillus sp Dad 13 produced sensorically acceptable youghurt and did not significantly different with traditional youghurtThe number of total lactic acid bacteria(LAB) increased during fermentation from 2.45x10 CFU/ml to 2.31 x 10 CFU/ml.Combination of L.bulgaricus and S.thermophilus starter cultures produced highest lactic acid production.However, supplementation of lactobacillus sp Dad 13 did not statically differenton latic acid production,pH and Lab count.Supplementation of probiotic bacteria is important in order to make yoghurt have a better functional food properties.